2015
DOI: 10.1128/aac.04548-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibiotic Susceptibilities of Yersinia pestis Determined by Broth Microdilution following CLSI Methods

Abstract: Y ersinia pestis is the causative agent of plague, a rare infection in humans that usually appears in the bubonic form due to flea bites. Pneumonic plague is an infection of the respiratory tract which can be contagious and rapidly fatal. This form of plague has an incubation period of 3 to 5 days and a mortality rate near 100% (1, 2). Antibiotic intervention can offer relief but only if started very early in the infection (1). Because of the scattered information on MICs under a variety of nonstandardized tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
(14 reference statements)
1
24
0
Order By: Relevance
“…(4,7,8). Furthermore, aminoglycosides are also active against the biothreat pathogens Yersinia pestis, the causative agent of pneumonic plague (9,10), and Francisella tularensis, the causative agent of tularemia (11,12). Class members also have potent activity against some Gram-positive organisms such as Staphylococcus spp., including methicillin-resistant (MRSA) and vancomycin-intermediate and -resistant Staphylococcus aureus isolates (4) and certain Mycobacterium spp.…”
Section: Spectrum Of Aminoglycoside Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…(4,7,8). Furthermore, aminoglycosides are also active against the biothreat pathogens Yersinia pestis, the causative agent of pneumonic plague (9,10), and Francisella tularensis, the causative agent of tularemia (11,12). Class members also have potent activity against some Gram-positive organisms such as Staphylococcus spp., including methicillin-resistant (MRSA) and vancomycin-intermediate and -resistant Staphylococcus aureus isolates (4) and certain Mycobacterium spp.…”
Section: Spectrum Of Aminoglycoside Activitymentioning
confidence: 99%
“…3B). There are 7 subclasses of phosphotransferases, specifically APH(2″), (3′), (3″) (4), (6), (7″), and (9). Several of these classes of enzymes are not relevant to clinical aminoglycoside resistance and are utilized for molecular genetics and cloning purposes in the laboratory.…”
Section: Phosphotransferasesmentioning
confidence: 99%
“…MICs were determined by the microdilution method in 96-well plates, as previously described (20), with the exception of the addition of IsoVitaleX (Becton Dickinson) to a final concentration of 2% (17,21). Antibiotics were serially diluted 2-fold in 50 l of cation-adjusted Mueller-Hinton broth (CAMHB).…”
mentioning
confidence: 99%
“…Its bactericidal activity is comparable to that of streptomycin, and its mode of administration is less restrictive; more acceptable for exposed population [ 24 ]. In addition, a wide range of antibiotics was already in vitro tested for their susceptibility to geographically diverse strains of Y. pestis which provide alternatives for plague treatment [ 25 ]. Another study had also investigated the susceptibility patterns of Y. pestis strains from diverse sources to 12 antimicrobial agents and showed that a large panel of Y. pestis remained susceptible not only to drugs traditionally used to treat plague (streptomycin, doxycycline and chloramphenicol), but also to newer agents (broad-spectrum cephalosporins and quinolones).…”
Section: Discussionmentioning
confidence: 99%